IMPACT OF SMOKING ON ANTI-PLATELET EFFECTS OF ASPIRIN - Noor, Mudassar; Nawaz, Usman; Khan, Saleem Ahmad; Waheed, Akbar; Altaf, Chaudhry (Pakistan Journal of Physiology, 2018)
Background: Cigarette smoking stimulates platelet activation and aggregation and can also influence adversely the antiplatelet effects of aspirin, which is the mainstay of treatment in the primary and secondary prevention of ischemic heart disease. This study was carried out to analyze the effect of smoking on aspirin efficacy in coronary heart disease patients. Methods: In this cross sectional analytical study, 384 ischemic heart disease patients were enrolled. Light transmission Aggregometry (LTA) with arachidonic acid was utilized to assess the platelet function. Data was analyzed using SPSS-23. Chi-square test Odds Ratio were utilized to find out association of smoking with aspirin response status. Results: The study contained 272 (70.8%) male and 112 (29.2%) females with the mean age of 48.22Â±11.87 years. There were 199 smokers (51.82%) and 185 non-smokers (48.18%). Frequency of aspirin resistant among smokers was 41 (20.60%) whereas the frequency in non-smokers was 12 (6.50) and the difference was significant (p<0.001). The adjusted Odds Ratio was 4.44 with 95% confidence interval of 2.07â€“8.90. Frequency comparison of aspirin responders between males and females was non-significant both in, smokers and non-smokers (p=0.14 and 0.92 respectively). Conclusion: Cigarette smoking adversely affects the antiplatelet efficacy of aspirin irrespective of gender.